Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

pls help me ,I couldnt solve these q1: if y=e x+e^x+e^x+...........∞ ,then dy/dx equals q2:if x=at 2 and y=2at then (xy*d 2 y/dx 2) is equal to thank u

pls help me ,I couldnt solve these


q1: if y=ex+e^x+e^x+...........∞,then dy/dx equals


q2:if x=at2 and y=2at then (xy*d2y/dx2)  is equal to


thank u

Grade:10

2 Answers

AKASH GOYAL AskiitiansExpert-IITD
419 Points
10 years ago

Dear Rishabh

I think there is some mistake in question 1

confirm the qustion and try to do it by taking log

question2

dy/dx= (dy/dt)/(dx/dt)

dy/dt=2a

dx/dt=2at

dy/dx=1/t

d2y/dx2= d/dx(dy/dx)

use chain rule

d2y/dx2= d/dt(dy/dx)*dt/dx

=d/dt(1/t)*1/2at

=-(1/t2)*1/2at

=-1/2at3

xyd2y/dx2=at2*2at*(-1/2at3)= -a

 

 All the best.                                                          

AKASH GOYAL

AskiitiansExpert-IIT Delhi

 

Please feel free to post as many doubts on our discussion forum as you can. We are all IITians and here to help you in your IIT JEE preparation.

Win exciting gifts by answering the questions on Discussion Forum. So help discuss any query on askiitians forum and become an Elite Expert League askiitian.

Now you score 5+15 POINTS by uploading your Pic and Downloading the Askiitians Toolbar  respectively : Click here to download the toolbar..

 

 

 

 

 

 

 

vikas askiitian expert
509 Points
10 years ago

1)

y=ex+e^x+e^x+...........∞

Y =ex+y 

dy/dx = ex+y(1+dy/dx)

dy/dx = (ex+y/1-ex+y )


2)

x=at2 ...........1

y=2at    ..............2

x/y = t/2   .........3

put t in eq 2

y = 4ax/y

y2 = 4ax

now differentiating above eq

2ydy/dx = 4a         .............1

again differentiating

2[(dy/dx)2 +yd2y/dx2] = 0        

d2y/dx2 = -(dy/dx)2/y          ..........2

multiply above eq by xy

(d2y/dx2)xy = -x(dy/dx)2

                      =-x(2a/y)2                    (from eq 1)

approve if u like my ans


Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free